Palaeomagnetism of early Cambrian Brigus red shale, eastern Newfoundland (Dataset) ... - Seguin, Maurice K.; Kunduri V. Rao (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Palaeomagnetism of early Cambrian Brigus red shale, eastern Newfoundland ...